Artificial Intelligence And Social Life Determinism - Jafar Mustafayev; Zebo Karshiboyeva (Open Academia, 2025)
Artificial intelligence (AI) has brought about a revolution in the ways we live, work, and interact with one another. As AI technology continues to advance, it becomes increasingly important to understand how artificial and natural intelligence function, as well as their goals, advantages, and limitations. This paper explores the world of artificial intelligence and examines several well-known categories and applications of AI services, while also discussing the potential future of AI across various fields
Keywords: Artificial intelligence; intelligent technologies; human effort